2015
DOI: 10.14202/vetworld.2015.449-452
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different egg quality traits and interpretation of their mode of inheritance in White Leghorns

Abstract: Aim:The experiment was carried out to evaluate different external and internal egg quality traits and to figure out their mode of inheritance from a set of hierarchically classified data.Materials and Methods:The data collected from 548 progenies (1 egg from each progeny) of 282 dams mated to 47 sires (1 sire mated to 6 dams) of a White Leghorn flock were used in the present study. Phenotypic means and their standard errors were calculated for all the quality traits. Heritabilities were estimated for these tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
31
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 11 publications
12
31
5
2
Order By: Relevance
“…The mean egg weight registered 55.02g at 25 weeks, 62.20g at 51 weeks and 63.29g at 72 weeks with a corresponding mean value of 60.17g for the overall ages of the hen depicting an increasing trend. These reports are similar to 57.78g registered by Rath et al [7] for egg weight at 50 weeks employing white leghorns; 48.1-63.9g reported for single Comb and white leghorn at 25 -65 weeks of age obtained by Chen et al [18]. Sreenivas et al [11] recorded 50.01 -53.89g for three pure lines and one control lines of white leghorns at 40 weeks.…”
Section: Phenotypic Least Square Means and Standard Error Of Egg Qualsupporting
confidence: 85%
See 4 more Smart Citations
“…The mean egg weight registered 55.02g at 25 weeks, 62.20g at 51 weeks and 63.29g at 72 weeks with a corresponding mean value of 60.17g for the overall ages of the hen depicting an increasing trend. These reports are similar to 57.78g registered by Rath et al [7] for egg weight at 50 weeks employing white leghorns; 48.1-63.9g reported for single Comb and white leghorn at 25 -65 weeks of age obtained by Chen et al [18]. Sreenivas et al [11] recorded 50.01 -53.89g for three pure lines and one control lines of white leghorns at 40 weeks.…”
Section: Phenotypic Least Square Means and Standard Error Of Egg Qualsupporting
confidence: 85%
“…Minelli et al [23] reported 6.00g at 28 -32 weeks, 6.16g at 47 -50 weeks and 6.29g at 70 -73 weeks of age. Rath et al [7] 6.00g at 50 weeks recorded for white leghorns. Tumova et al [33] obtained 6.91 -7.81g at 28 -60 weeks of age in New Black breed; and 6.50 -6.91g for litter raised Hisex Brown at 60 weeks.…”
Section: Phenotypic Least Square Means and Standard Error Of Egg Qualmentioning
confidence: 95%
See 3 more Smart Citations